1992
DOI: 10.1128/jb.174.4.1410-1413.1992
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-derived oligosaccharides affect porin osmoregulation only in media of low ionic strength

Abstract: Gram-negative bacteria grown under conditions of low osmolarity accumulate significant amounts of periplasmic glucans, membrane-derived oligosaccharides (MDO) in Escherichia coli and cyclic glucans in members of the family Rhizobiaceae. It was reported previously (W. Fiedler and H. Rotering, J. Biol. Chem. 263:14684-14689, 1988) (20). The synthesis of MDO in E. coli and of cyclic glucans in the Rhizobiaceae is a striking example of osmoregulation, being about 10-fold higher during growth in a medium of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…21 It is possible that the osmo-remedial strains are unable to respond to low osmolality by synthesis of MDO and ompF. This is supported, in part, by the finding that ompF was increased by nicotinamide under hypotonic conditions.…”
Section: Discussionsupporting
confidence: 70%
“…21 It is possible that the osmo-remedial strains are unable to respond to low osmolality by synthesis of MDO and ompF. This is supported, in part, by the finding that ompF was increased by nicotinamide under hypotonic conditions.…”
Section: Discussionsupporting
confidence: 70%
“…Included in this group are the two mutants with transposon insertions in mdoH and mdoG, which encode membrane-derived oligosaccharides (MDOs). MDOs are branched substituted b-glucan chains present in the periplasm of various Gramnegative bacteria and their expression increases in lowosmolarity medium (Geiger et al, 1992). The MDO mutants tend to suffer pleiotropic effects, most likely due to altered membrane properties, which may account for the requirement for MDOs by a variety of plant and animal pathogens for virulence (Bhagwat et al, 2004;Page et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Kennedy and coworkers (42,69,70) have indicated that the accumulation of MDO within the periplasm may be advantageous during growth at low osmolarity for the following reasons: (i) the accumulation of these molecules provides a mechanism for the cell to regulate the relative volumes of periplasmic and cytoplasmic compartments; (ii) anionic MDO contribute to the ionic strength of the periplasm, which appears to be important for porin regulation (33) and possibly other processes; (iii) high concentrations of MDO within the periplasm should lead to a reduction in turgor pressure across the cytoplasmic membrane; and (iv) the accumulation of anionic MDO within the periplasm should lead to the development of a Donnan potential across the outer membrane.…”
Section: Hypoosmotic Adaptationmentioning
confidence: 99%
“…How the periplasmic cyclic ,B-glucans could influence the structure of the cell envelope is unclear; however, one possible mechanism is through interactions with other cell envelope components such as membrane proteins. Evidence to support this possibility is derived from recent studies with E. coli that have indicated an influence of MDO on outer membrane porin synthesis and activity (33,42).…”
Section: Interactionsmentioning
confidence: 99%